Stethoscope as potential occupational hazards for intra hospital carries of pathogenic microorganisms - sahb, Ali Abd Ali (AL-Kindy College Medical Journal, 2019)
Background: The stethoscope is a tool that doctors use daily in the examination of patients and  it  can take part in the transmission of health care-associated infections. In a single day it may come in direct contact with multiple patients and the intra hospital environment  may be contaminated by various type of bacteria and possibly transmit to others.Objective:- The study was to know the attitude and knowledge about   the stethoscope hygiene behavior among physicians  and to determine the types of  bacterial agents that can contaminate stethoscopes.Type of the study: The study was a cross-sectional studyMethods:-  It was conducted from 1st of July to end of October 2014 at AL-Emmamain Alkadhomain Medical City in which a convenient sample of 150 physicians  were included. A semi constructed questionnaire was used to collect demographic data and hygiene practice among participants. Specimen was collected using moisten sterile cotton swab and then cultured following standard microbiological techniques. The results:- showed a total of 121 (80.6%) of the stethoscopes had bacterial contamination only 29(19.40%) had negative cultures. There is statistically significant association between stethoscope contamination and frequency of cleaning it. Of the studied group only 26 subjects (17.3%) received education regarding stethoscope cleaning.Conclusion:-There was evidence that bacteria can transfer from the skin of the patient to the stethoscope and from the stethoscope to the skin and there was poor education and assessing cleaning practices of stethoscopes.